(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
According to Fermat’s little theorem, for any p is a prime integer and (, ) = 1, then the congruence −1 ≡ 1( )is true, if we remove the restriction that (, ) = 1, we may declare−1 ≡ ( ). For every integer x. Euler extended Fermat’s Theorem as follows: if (, ) = 1,then,where () ≡ 1( ). is Euler’s phi-function. Euler’s theorem cannot be implemented for any every integers x in the same manners as Fermat’s theorem works; that is, the congruence ()+1 ≡ ( ) is not always true. In this paper, we discussed the validation of congruence ()+1 ≡ ( ).